From illegalised migrant toward permanent resident: assembling precarious legal status trajectories and differential inclusion in Canada. Issue 1 (2nd January 2022) - Goldring, Luin; Landolt, Patricia
ABSTRACT: Precarious legal status trajectories (PLSTs) are marked by periods without state authorisation and/or forms of temporary authorisation. They are temporally prolonged and directionally unpredictable, and may be spatially, juridically and substantively discontinuous. Their complexity poses challenges for researchers interested in the relationship between changes in legal status and differential inclusion. We examine the trajectories of illegalised Anglo-Caribbean and Latin American migrants living in Canada in the mid-2000s who applied for one or both of two humanitarian legal status adjustment mechanisms to obtain permanent residence: late refugee claims and applications on humanitarian and compassionate grounds. Despite sharing early illegalisation, we find regional racialised and gendered differences in their PLSTs. We present a framework for understanding how different trajectories are populated, and how the somewhat unpredictable outcomes of adjudications may lead to further applications and a reorganisation of PLSTs. We conceptualise PLSTs as assembled through (1) colonial legacies and histories of migration that contribute to racialised humanitarian deservingness, (2) state policies and humanitarian adjudication procedures, and (3) everyday encounters between migrants and other social and institutional actors. Our analysis shows how these elements come together and generate variable PLSTs and multi-dimensional differential inclusion.